Pengaruh Suku Bunga, Nilai Tukar USD/IDR, Indeks Dow Jones Terhadap Volatilitas Return Pasar Modal Indonesia (Indeks LQ45) - Yanti, Agus B1021161001 (Jurnal Manajemen Update, 2020)
This study aims to examine and analyze the effect of Interest Rates, Exchange Rates USD/IDR, and the Dow Jones Index on the volatility of the Indonesian Capital Market return, which is presented with the LQ45 index. Analysis of the data used to analyze is GARCH analysis. The results show that interest rates have an insignificant negative relationship to the volatility of Indonesian capital market returns (LQ45 index). The exchange rate has a significant negative relationship, while the dow jones index has a significant positive relationship to the volatility of the Indonesian capital market return (LQ45 index). The ability of these variables to explain their effects on the volatility of Indonesian capital market returns (LQ45 index) is 10 per cent. In contrast, other factors outside the research model explain the remaining 90 per cent.Â Keywords: LQ45 Index, Interest Rates, Exchange Rates, Dow Jones IndexDAFTAR PUSTAKAAlwi , Z. I. (2008). Pasar Modal Teori dan Aplikasi. Jakarta: Yayasan Pancur Siwah.Ang, R. (1997). Buku Pintar Pasar Modal Indonesia. Jakarta: Media Staff Indonesia.Ardana , Y. (2016). Analisis Pengaruh Variabel Makroekonomi Terhadap Indeks Saham Syariah Indonesia (Periode Mei 2011-September 2015 Dengan Model ECM). Jurnal Ekonomi, Bisnis & Entrepreneurship Vol.10, No. 1, 76-90.Arikunto. (2006). Prosedur Penelitian Suatu Pendekatan Praktek. Jakarta: PT Rineka Cipta.Basarda, R. F., Moeljadi, & Indrawati , N. K. (2018). Macro and Micro Determinants of Stock Return Companies in LQ-45 Index. Jurnal Keuangan dan Perbankan, 310-320.Butt, B. Z., Rehman, K. U., Khan, M. A., & Safwan, N. (2010). Do economic factors influence stock returns? A firm and industry level analysis . African Journal of Business Management Vol. 4, 583-593.Fahmi, I. (2012). Analisis Kinerja Keuangan. Bandung: Alfabeta.Ferdinand, A. (2011). Metode Penelitian Manajemen Pedoman Penelitian untuk Penulisan Skripsi, dan Disertasi Ilmu Manajemen, Edisi 3. Semarang: Badan Penerbit Universitas Diponegoro.Hadi, N. (2015). Pasar Modal Edisi 2. Yogyakarta: Graha Ilmu.Hardanto, S. S. (2006). Manajemen Risiko Bagi Bank Umum. Jakarta: Elek Media Komputindo.Husnan , S. (1994). Dasar-Dasar Teori Portofolio dan Analisis Sekuritas . Yogyakarta: UPP AMP YKPN.Imbayani , I. A. (2015). Analisis Pengaruh Indeks Dow Jones, Indeks Strait, Times Indeks Nikkei 225, Indeks Hang Seng, Dan Kurs Rupiah Terhadap Indeks Harga Saham Gabungan Di Bursa Efek Indonesia. Juima Vol. 5 No. 1, 12-21.Jayanti , Y., Darminto, & Sudjana , N. (2014). Pengaruh Tingkat Inflasi, Tingkat Suku Bunga SBI, Nilai Tukar Rupiah, Indeks Dow Jones, Dan Indeks KLSE Terhadap Indeks Harga Saham Gabungan (IHSG) Studi Pada Bursa Efek Indonesia Periode Januari 2010 â€“ Desember 2013. Jurnal Administrasi Bisnis (JAB) Vol. 11 No. 1, 1-10.Jogiyanto, H. (2017). Teori Portofolio dan Analisis Investasi Edisi Kesebelas. Yogyakarta: BPFE.Kabeer , M. A., Iqbal , A., Najaf , R., & Najaf , K. (2016). The Influences of Macro-Economic Factors on Capital Market Performance in Pakistan . Journal of Poverty, Investment and Development Vol.21, 79-85.Kerlinger. (2006). Asas-Asas Penelitian Behavioral. Yogyakarta: Gadjah Mada University Press.Kumalasari , R., Hidayat , R. R., & Azizah , D. F. (2016). Pengaruh Nilai Tukar, Bi Rate, Tingkat Inflasi, Dan Pertumbuhan Ekonomi Terhadap Indeks Harga Saham Gabungan (Studi Pada Indeks Harga Saham Gabungan di BEI Periode Juli 2005-Juni 2015). Jurnal Administrasi Bisnis (JAB) Vol. 34, 130-137.Madura , J. (2000). Manajemen Keuangan Internasional Edisi 4 Jilid 1. Jakarta : Erlangga.Mankiw N, G. (2006). Makro Ekonomi, Terjemaha: Fitria Liza, Imam Nurmawan. Jakarta: Erlangga.Mayzan , M. B., & Sulasmiyati , S. (2018). Pengaruh Kurs Rupiah, Bi Rate, Net Foreign Fund dan Indeks Dow Jones Terhadap Indeks Harga Saham Gabungan. Jurnal Administrasi Bisnis (JAB) Vol. 56 No. 1 , 10-19.Mohammad , G., Ullah, W., Islam, A., Alam, M. S., & Khan, M. K. (2017). Effect of Macroeconomic Variables On Stock Market Performance Of SAARC Countries. Asian Economic and Financial Review Vol.7, 770-779.Muhamad, F. (2009). Metode Penelitian Kuantitatif. Semarang: Walisongo Press.Murthy, U., Anthony, P., & Vighnesvaran , R. (2017). Factors Affecting Kuala Lumpur Composite Index (KLCI) Stock Market Return in Malaysia . International Journal of Business and Management; Vol. 12, No. 1, 122-132.Nachrowi, N. D., & Usman, H. (2006). Pendekatan Populer dan Praktis Ekonometrika Untuk Analisis Ekonomi dan Keuangan. Jakarta : Lembaga Penerbit Fakultas Ekonomi Universitas Indonesia.Nidianti, P. I. (2013). Pengaruh Faktor Internal dan Eksternal Perusahaan Terhadap Return Saham Food & Beverages di Bursa Efek Indonesia. E-Jurnal Akuntansi Universitas Udayana 5, 130-146.Ningsih, M. M., & Waspada , I. (2018). Pengaruh BI Rate dan Inflasi Terhadap Indeks Harga Saham Gabungan (Studi Pada Indeks Properti, Real Estate, Dan Building Construction, di BEI Periode 2013 - 2017) . Manajerial, Vol. 3 No.5 , 247-258.Putra Asmara, I. W., & Suarjaya , A. G. (2018). Pengaruh Variabel Makro Ekonomi Terhadap Indeks Harga Saham Gabungan. E-Jurnal Manajemen Unud, Vol. 7, No. 3 ISSN : 2302-8912, 1397-1425.Rosadi, D. (2012). Ekonometrika dan Analisis Runtun Waktu Terapan dengan Eviews. Yogyakarta: C.V. Andi Offse.Samuelson, P. A., Nordhaus, & William, D. (2004). Ilmu Makro Ekonomi. Jakarta: PT Media Edukasi.Sartono, A. (2001). Manajemen Keuangan Teori dan Aplikasi. Yogyakarta: BPEF-YOGYAKARTA.Setyawasih, R. (2009). Analisis Pemodelan Pengujian Eksistensi Anomaly return Harian Saham di Bursa Efek Indonesia. Jurnal Optimal Vol.3, 15-28.Silim, L. (2013). Pengaruh Variabel Ekonomi Makro Terhadap Indeks Harga Saham Gabungan Pada Bursa Efek Indonesia Periode 2002-2011. Jurnal Ilmiah Mahasiswa Universitas Surabaya Vol.2 No.2, 1-18.Sugiyono. (2010). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sumiyana. (2008). Day Of The Week dan Monday Effect: Fenomena Yang Terbuktikan Tidak Konsisten di Pasar Modal Indonesia. Jurnal Manajemen Teori dan Terapan 1 .Sunariyah. (2006). Pengantar Pengetahuan Pasar Modal. Yogyakarta: UPP STIM YKPN.Tandelilin, E. (2010). Portofolio dan Investasi Teori dan Aplikasi. Yogyakarta: Kanisius.Wicaksono, I. S., & Yasa, G. W. (2017). Pengaruh Fed Rate, Indeks Dow Jones, Nikkei 225,Hang Seng Terhadap Indeks Harga Saham Gabungan. E-Jurnal Akuntansi Universitas Udayana Vol.18.1., 358-385.Widoatmojo, S. (2007). Cara Sehat Investasi di Pasar Modal. Jakarta: PT Elex Media Komputindo.Wismantara, S. Y., & Darmayanti, N. A. (2017). Pengaruh Nilai Tukar, Suku Bunga Dan Inflasi Terhadap Indkes Harga Saham Gabungan Di Bursa Efek Indonesia. E-Jurnal Manajemen Unud, Vol. 6, No. 8, 4391-4421.